Organization, Structure, and Variability of the rRNA Operon of the Whipple's Disease Bacterium (Tropheryma whippelii) - Maiwald, Matthias (American Society for Microbiology, 2000)
Whipple's disease is a systemic disorder associated with a cultivation-resistant, poorly characterized actinomycete, Tropheryma whippelii. We determined a nearly complete rRNA operon sequence of T. whippelii from specimens from 3 patients with Whipple's disease, as well as partial operon sequences from 43 patients. Variability was observed in the 16S-23S rRNA spacer sequences, leading to the description of five distinct sequence types. One specimen contained two spacer sequence types, raising the possibility of a double infection. Secondary structure models for the primary rRNA transcript and mature rRNAs revealed rare or unique features.